1988
DOI: 10.1507/endocrj1954.35.255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Spermatogenesis of Rana Hexadactyla(Lesson).

Abstract: It has been reported that melatonin produces either progonadal or antigonadal effects in mammals, depending on the time and mode of administration. Information on the melatonin-effect on the testis in toads indicated varied changes during the breeding and hibernating seasons. The present study in Rana hexadactyla (Lesson), a continuous breeder revealed that administration of melatonin at a dosage of 50 micrograms/frog/day either in the morning or evening for a week inhibited spermatogenesis; however, when mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…The results of the present study revealed that a 50 mg/kg exposure to cadmium induces significant apoptosis of spermatogonia and spermatocytes in the testes of adult Iberian ribbed newts, indicating that germ cells in these differentiation stages are highly sensitive to cadmium. The histopathologic findings of the present study are similar to those reported for cadmium-exposed frogs, such as B. melanostictus and R. hexadactyla Lesson , and fish, such as O. latipes 24 , 25 , 26 . To our knowledge, this is the first report of the histomorphologic characteristics of cadmium-induced testicular dysfunction in newts.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The results of the present study revealed that a 50 mg/kg exposure to cadmium induces significant apoptosis of spermatogonia and spermatocytes in the testes of adult Iberian ribbed newts, indicating that germ cells in these differentiation stages are highly sensitive to cadmium. The histopathologic findings of the present study are similar to those reported for cadmium-exposed frogs, such as B. melanostictus and R. hexadactyla Lesson , and fish, such as O. latipes 24 , 25 , 26 . To our knowledge, this is the first report of the histomorphologic characteristics of cadmium-induced testicular dysfunction in newts.…”
supporting
confidence: 88%
“…injection of 50 mg/kg of cadmium induced apoptosis of the spermatogonia and spermatocytes in Iberian ribbed newts. The observed histopathologic findings in the testes of newts exposed to cadmium were similar to those reported for testes of several frogs, such as Bufo melanostictus and Rana hexadactyla Lesson 24 , 25 , and fish, such as Oryzias latipes 26 .…”
supporting
confidence: 84%
“…Another study carried out by Kasinathan et al [29] showed that Cd significantly reduces primary and secondary spermatocyte in seminiferous tubules.…”
Section: Groups Mean Johnsen Scorementioning
confidence: 95%
“…Exposure to cadmium can induce germ cell apoptosis, which may account for the current decline in male fertility ( Akinloye et al, 2006 ). Another study, carried out by Kasinathan et al . (1987) showed that cadmium significantly decreased primary and secondary spermatocytes in the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%